Individualized positive end-expiratory pressure guided by driving pressure in robot-assisted laparoscopic radical prostatectomy: a prospective, randomized controlled clinical trial - Luo, Yanfang; Qin, Siyu; Liu, Mengxiao; Shen, Qian; An, Ran; Jiang, Yan (Frontiers in Medicine, 2025)
BackgroundDespite the widespread use of lung-protective ventilation in general anesthesia, the optimal positive end-expiratory pressure (PEEP) remains uncertain. This study aimed to investigate the effects of driving pressure-guided individualized PEEP in patients undergoing robot-assisted laparoscopic radical prostatectomy.MethodsForty-two male patients undergoing robot-assisted laparoscopic radical prostatectomy were randomized to receive conventional fixed PEEP of 5 cmH2O (n = 21, PEEP5) or driving pressure-guided individualized PEEP (n = 21, PEEPIND). The primary outcome was the ratio of arterial oxygen partial pressure to fractional inspired oxygen (PaO2/FiO2). The secondary outcomes included respiratory mechanics, hemodynamics, optic nerve sheath diameter (ONSD), and the incidence of postoperative delirium (POD) and postoperative pulmonary complications (PPCs) within a 7-day period.ResultsIn comparison with the PEEP5 group, the PEEPIND group showed significantly higher (p < 0.001) PEEP values during pneumoperitoneum in the Trendelenburg position (mean [standard deviation], 11.29 cmH2O [1.01 cmH2O]) and after deflation and repositioning to the supine position (mean [standard deviation], 7.05 cmH2O [1.20 cmH2O]). The PaO2/FiO2 values in the PEEPIND group were significantly higher than those in the PEEP5 group 120 min after pneumoperitoneum in the Trendelenburg position (p = 0.023) and at the end of the operation (p = 0.028). The groups showed no differences in ONSD, hemodynamics, and incidence of POD and PPCs (p > 0.05).ConclusionIn comparison with a fixed PEEP of 5 cmH2O, driving pressure-guided individualized PEEP improves intraoperative respiratory mechanics and oxygenation without causing deterioration in hemodynamics, further escalation in intracranial pressure, or an increase in the incidence of POD. Nevertheless, this procedure requires meticulous monitoring. Unfortunately, individualized PEEP did not result in a reduction in the incidence of PPCs in this study.Clinical Trial Registrationhttp://www.chictr.org.cn, ChiCTR2400081338.